Lactococcus lactis spp lactis infection in infants with chronic diarrhea: two cases report and literature review in children - KEPENEKLİ KADAYİFCİ, EDA; ÜLGER, NURVER; YAKUT, NURHAYAT (My University, 2016)
Lactococcus lactis is a gram-positive, facultative anaerobic coccus that is occasionally isolated from human mucocutaneous surfaces such as the intestines. It is used in the dairy industry for milk acidification and is mostly nonpathogenic in immunocompetent humans, however a number of cases of infection with L. lactis have been reported in recent years. In this article, we describe two cases of infection due to L. lactis in patients with chronic diarrhea. The first case is a five-month-old boy who was operated on for volvulus on his first day of life and had ileostomy with subsequent diagnosis of chronic diarrhea and bacteremia due to L. Lactis. The second case is a six-month-old girl with the diagnosis of chronic diarrhea that developed after a catheter-related bloodstream infection. Both of the infections due to L. Lactis spp lactis were successfully treated with intravenous vancomycin therapy. Although Lactococcus species is mostly known as nonpathogenic, it should be kept in mind as a potential pathogen, especially in patients with gastrointestinal disorders.
Lactococcus lactis spp lactis infection in infants with chronic diarrhea